Blood lactate response to 30 s arm cranking and leg cycling in elite wrestlers - Lutoslawska, G.; Hübner-Wozniak, E.; Kosmol, A. (Medicina Sportiva, 2003)
The aim of the present study was to examine post-exercise blood lactate concentration in response to 30 s leg cycling and arm cranking in elite wrestlers. A total of 33 free and Greco-Roman style wrestlers participated in the study. All subjects underwent 30 s leg cycling and 30 s arm cranking. Blood lactate concentrations were determined 3, 5, 7, 9, 13 and 30 min after the exercise. Absolute and relative mean and peak power output during leg cycling (606.4±185.5 W and 8.6±0.5 W . kg-1 for mean power and 844.1±166.9 W and 11.3±0.7 W . kg -1 for peak power) was significantly greater than during arm cranking (482.9±170.9 W and 6.9±0.5 W . kg -1 for mean power and 666.9±242.3 W and 9.7±0.1 W . kg -1 for peak power). However, post-exercise blood lactate concentration measured 3-30 min after exercise did not differ following both exercises. Average blood lactate levels (sum of lactate concentration determined 3-30 min after the exercise) was also similar in response to arm cranking (62.5±10.6 mmol . l -1) and leg cycling (61.4±11.5 mmol . l -1). On the other hand, total post-exercise blood lactate expressed per 1 W of the absolute mean power output after arm cranking (0.122±0.025 mmol . l -1 . W -1) was significantly greater than after leg cycling (0.099±0.019 mmol . l .1 . W -1). Multiple regression analysis revealed that peak post-exercise blood lactate concentration was significantly correlated with relative peak power output during arm cranking and leg cycling (partial correlation coefficient r= 0.61 and r= 0.37 for leg and arm exercise, respectively). We conclude that post-exercise blood lactate concentration following 30 s arm cranking is exaggerated in comparison with leg cycling. Additionally, peak post-exercise blood lactate response to both leg cycling and arm cranking in wrestlers of the present study reflects peak power during upper and lower body supramaximal work.